TCF1 and LEF1 promote B-1a cell homeostasis and regulatory function - Qian Shen; Hao Wang; Jonathan A. Roco; Xiangpeng Meng; Marita Bosticardo; Marie Hodges; Michael Battaglia; Zhi-Ping Feng; Benjamin James Talks; Jason Powell; Vijaya Baskar Mahalingam Shanmugiah; Julia Chu; et al. (Nature, 2025)
Abstract B-1 cells are innate-like immune cells abundant in serosal cavities with antibodies enriched in bacterial recognition, yet their existence in humans has been controversial 1–3 . The CD5 + B-1a subset expresses anti-inflammatory molecules including IL-10, PDL1 and CTLA4 and can be immunoregulatory 4–6 . Unlike conventional B cells that are continuously replenished, B-1a cells are produced early in life and maintained through self-renewal 7 . Here we show that the transcription factors TCF1 and LEF1 are critical regulators of B-1a cells. LEF1 expression is highest in fetal and bone marrow B-1 progenitors, whereas the levels of TCF1 are higher in splenic and peritoneal B-1 cells than in B-1 progenitors. TCF1–LEF1 double deficient mice have reduced B-1a cells and defective B-1a cell maintenance. These transcription factors promote MYC-dependent metabolic pathways and induce a stem-like population upon activation, partly via IL-10 production. In the absence of TCF1 and LEF1, B-1 cells proliferate excessively and acquire an exhausted phenotype with reduced IL-10 and PDL1 expression. Furthermore, adoptive transfer of B-1 cells lacking TCF1 and LEF1 fails to suppress brain inflammation. These transcription factors are also expressed in human chronic lymphocytic leukaemia B cells and in a B-1-like population that is abundant in pleural fluid and circulation of some patients with pleural infection. Our findings define a TCF1–LEF1-driven transcriptional program that integrates stemness and regulatory function in B-1a cells.